(untitled) (IIUC Studies, 2021)
Most of the IoT applications require real time and secure exchange of information among connected devices and hence, currently, security of communication protocols is becoming key topic of research. MQTT, a lightweight communication protocol, is used for real time communication between networks. Authors have reviewed numerous published researches on secure MQTT protocol for IoT networks and have discovered security loop holes of MQTT communication protocol that are needed to be addressed. This article proposes a secure and real time MQTT protocol by incorporating SSL certificate to MQTT broker for IoT applications without data loss. The research has been implemented in Raspberry Pi 3B system using Python 3.4.10 development platform along with Numpy 1.11.1 and scipy 0.18.0 (for mathematical analysis), paho-mqtt 1.5.0 (for MQTT publication/subscription), and Chromium (for displaying research outcome). The outcome of this research shows that the proposed MQTT protocol has tighten security during exchanging information over IoT networks without any loss of data. IIUC Studies Vol.17, December 2020: 27-42